ALL-RUSSIAN THEORETICAL/PRACTICAL CONFERENCE WITH INTERNATIONAL PARTICIPATION «PHARMACOTHERAPY AND DIETETICS IN PEDIATRICS» - article Editorial (Union of pediatricians of Russia, 2015)
ALL-RUSSIAN THEORETICAL/PRACTICAL CONFERENCE WITH INTERNATIONAL PARTICIPATION «PHARMACOTHERAPY AND DIETETICS IN PEDIATRICS»